Late Failing Heart Allografts: Pathology of Cardiac Allograft Vasculopathy and Association With Antibody‐Mediated Rejection. Issue 1 (20th November 2015) - Loupy, A.; Toquet, C.; Rouvier, P.; Beuscart, T.; Bories, M. C.; Varnous, S.; Guillemain, R.; Pattier, S.; Suberbielle, C.; Leprince, P.; Lefaucheur, C.; Jouven, X.; et al.
Abstract : In heart transplantation, there is a lack of robust evidence of the specific causes of late allograft failure. We hypothesized that a substantial fraction of failing heart allografts may be associated with antibody‐mediated injury and immune‐mediated coronary arteriosclerosis. We included all patients undergoing a retransplantation for late terminal heart allograft failure in three referral centers. We performed an integrative strategy of heart allograft phenotyping by assessing the heart vascular tree including histopathology and immunohistochemistry together with circulating donor‐specific antibodies. The main analysis included 40 explanted heart allografts patients and 402 endomyocardial biopsies performed before allograft loss. Overall, antibody‐mediated rejection was observed in 19 (47.5%) failing heart allografts including 16 patients (40%) in whom unrecognized previous episodes of subclinical antibody‐mediated rejection occurred 4.5 ± 3.5 years before allograft loss. Explanted allografts with evidence of antibody‐mediated rejection demonstrated higher endothelitis and microvascular inflammation scores (0.89 ± 0.26 and 2.25 ± 0.28, respectively) compared with explanted allografts without antibody‐mediated rejection (0.42 ± 0.11 and 0.36 ± 0.09, p = 0.046 and p < 0.0001, respectively). Antibody‐mediated injury was observed in 62.1% of failing allografts with pure coronary arteriosclerosis and mixed (arteriosclerosis and atherosclerosis) pattern, while it was not observed in patients with pure coronary atherosclerosis (p = 0.0076). We demonstrate that antibody‐mediated rejection is operating in a substantial fraction of failing heart allografts and is associated with severe coronary arteriosclerosis. Unrecognized subclinical antibody‐mediated rejection episodes may be observed years before allograft failure. Abstract : This study demonstrates that antibody‐mediated rejection operates in a substantial fraction of late chronic failing heart allografts, including unrecognized subclinical antibody‐mediated rejection episodes observed years before allograft failure. See Burke's editorial onpage 9 .